GENERATIVE AI AND ESP WRITING INSTRUCTION IN A HIGH-CONTEXT ENGINEERING CULTURE: A CASE STUDY IN AN INDONESIAN MANUFACTURING INDUSTRY - Fikri Asih Wigati; Fika Natasya Rahma (Indonesian EFL Journal, 2026)
The swift evolution of generative artificial intelligence (AI) has heightened the necessity to reevaluate writing instruction in English for Specific Purposes (ESP), especially within high context culture environments. This qualitative case study examines three interconnected dimensions of AI integration in genrebased writing instruction for English Specific Purposes (ESP) training within an Indonesian metal industry: the interpretation and application of AI by ESP Teachers in the design of genre-specific writing instruction, the utilization of AI by trainees in the creation of technical documents, and the adaptation of assessment methodologies in the high context culture environment. Data were gathered via comprehensive interviews with 20 managers in the manufacturing industry, classroom observations, and the examination of instructional artifacts. The results show that teachers mostly see AI as a way to help them make genre models and make sure that their teaching materials meet the needs of communication in the field due to the specific knowledge and practices in metal industry. This article also reveals how writing instruction in an ESP metal industry classroom unfolds when AI is integrated within a high-context cultural setting, illustrating the dynamic interplay between technological tools and culturally embedded communication norms. The finding indicates a framework through which the assessment of trainees' writing skill development can be effectively conducted within the context. This study enriches contemporary and empirical insights into AI-integrated genre-based English for Specific Purposes (ESP) instruction within the underrepresented context of the metal industry in a high-context culture.